2006
DOI: 10.1007/s11244-006-0035-4
|View full text |Cite
|
Sign up to set email alerts
|

Non-oxidative methane transformations into higher hydrocarbons over bimetallic Pt–Co catalysts supported on Al2O3 and NaY

Abstract: The methane conversion under non-oxidative conditions over Al 2 O 3 and NaY supported cobalt, platinum and Pt-Co bimetallic catalysts in a flow system has been investigated. The two-step process was applied in the temperature range between 523 and 673 K and 1 bar pressure and the one-step process was carried out under the conditions of 1073 K and 10 bar pressure. Addition of platinum to NaY and alumina supported cobalt samples results in the formation of metallic Co particles and Pt-Co bimetallic particles. On… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…Many reports have indicated that alloying Pt with another nonnoble metal can not only lower the cost but also effectively improve the catalytic properties of Pt NPs. 49,[57][58][59][60][61][62][63][64][65][66][67][68][69][70] Bimetallic Pt-Ni NPs (undefined Pt-Ni structure) containing 0.5 wt% Pt and 20 wt% Ni have been prepared on activated carbon cloth (ACC) support for dehydrogenation of cyclohexane to benzene. The synergistic effect between Pt and Ni was obvious: the hydrogen production was enhanced by ca.…”
Section: Alloy Nps Combining Noble and Non-noble Metalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many reports have indicated that alloying Pt with another nonnoble metal can not only lower the cost but also effectively improve the catalytic properties of Pt NPs. 49,[57][58][59][60][61][62][63][64][65][66][67][68][69][70] Bimetallic Pt-Ni NPs (undefined Pt-Ni structure) containing 0.5 wt% Pt and 20 wt% Ni have been prepared on activated carbon cloth (ACC) support for dehydrogenation of cyclohexane to benzene. The synergistic effect between Pt and Ni was obvious: the hydrogen production was enhanced by ca.…”
Section: Alloy Nps Combining Noble and Non-noble Metalsmentioning
confidence: 99%
“…The synergy in the bimetallic system can be explained by the enhanced reducibility of cobalt, increased metal surface (higher dispersion) and the cooperation of two types of active components (Co facilitates the chaingrowth of partially dehydrogenated species produced on Pt in Pt-Co bimetallic NPs). 63 Ko et al have reported that a Pt-Co bimetallic catalyst supported on yttria-stabilized zirconia (YSZ) was highly efficient for preferential CO oxidation (PROX) in a H 2 -rich gas stream even with a small amount of Pt (0.5 wt%) at temperatures below 423 K. By optimizing the calcination and reduction pre-treatment conditions for Pt-Co/YSZ, the CO concentration can be decreased below 10 ppm in the temperature range of 380-423 K. 64 Highly dispersed Pt-Cu nanocrystals with 2 nm size were supported on Mg 3 Si 2 O 5 (OH) 4 nanotubes or CeO 2 , both of which showed enhanced performances compared to pure noble metal nanocrystals with similar sizes in the CO oxidation. 66 The combination of Pt and Sn metals, giving Pt-Sn bimetallic NPs supported on mesoporous carbon, have exhibited considerably higher conversion and selectivity in both the hydrogenation reaction of cinnamaldehyde to cinnamyl alcohol and the dehydrogenation reaction of propane to propylene, for the latter of which the presence of Sn resulting in higher Pt dispersion and weaker adsorption affinity of hydrocarbons on the surface Pt sites in Pt-Sn NPs may be responsible for the superior activity, selectivity and stability.…”
Section: Alloy Nps Combining Noble and Non-noble Metalsmentioning
confidence: 99%
“…10 Accounts reporting heavy hydrocarbon formation from CH 4 are predominantly based upon supported metal systems. [11][12][13] For instance Re and Mo supported on H-ZSM-5 convert CH 4 mainly to aromatics, with the selectivity to C 2 H 6 being less than 7%. [14][15][16] Recently, we reported exceptionally selective coupling of methane to hydrogen and ethane at moderate temperature in a simple fixed-bed reactor catalyzed by Ta-H supported on silica.…”
mentioning
confidence: 99%
“…S1, ESIw). 11 To enhance the CH 4 conversion, a hydrogen selective membrane reactor can be used in order to shift the equilibrium in eqn (1) to the right hand side by constant removal of hydrogen. 24 Considerable research efforts have been devoted to the development of various membrane reactors based on separating/removing the products out of the reaction zone to improve the yield of desired product.…”
mentioning
confidence: 99%
“…16 Nowadays, there is a general interest in developing highly catalytically active bimetallic and multimetallic catalysts containing first-row transition nonnoble metal, such as Fe, Co, Ni, and so on, to catalyze the hydrolysis of NaBH 4 with high efficiency. [17][18][19] However, the success in their application highly depends on the stability of the nanoparticles because of their high tendency to form agglomerates and their extreme reactivity toward water and oxygen. 20 21 In the present work, we describe the syntheses, characterization of PVP-protected Pt/Ni bimetallic nanoparticle (BNP) catalysts as well as their catalytic activities for hydrogen generation from the hydrolysis of a basic NaBH 4 solution. )…”
Section: Introductionmentioning
confidence: 99%